Pengaruh Terapi Musik Terhadap Penurunan Kecemasan Pasien Pre Kateterisasi Jantung - Budi, Arif Wahyu Setyo; Jumaiyah, Wati; Fajarini, Melati; Tyawarman, Ady (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of music therapy on reducing anxiety in pre-cardiac catheterization patients. The method used is quantitative with a quasi-experimental design. The data collection technique uses an anxiety questionnaire, namely HARS (Hamilton Rating Scale). The data analysis technique uses paired sample t-test. The results of the study showed that there was an effect of music therapy on reducing anxiety in pre-cardiac catheterization patients (p<0.05), where this was indicated by a significant difference in anxiety scores before and after giving music therapy. In conclusion, there is an effect of providing music therapy on reducing anxiety in pre-cardiac catheterization patients. Keywords: Anxiety, Cardiac Catheterization, Music Therapy.